Pursed Lip Breathing Therapy and Semi-Fowler Position to Reduce Shortness of Breath in Asthma: Case Study - Heriyanto, Hendri; Mardiani, Mardiani (Jurnal Ilmiah Ners Indonesia, 2025)
Bronchial asthma is a non-infectious disease characterized by the narrowing of the respiratory tract due to excessive activity in response to certain stimuli. The prevalence of asthma in Indonesia is 13 per 1,000 population. The highest incidence of asthma is in Central Sulawesi at 7.8% and in East Nusa Tenggara at 7.3%. Risk factors for bronchial asthma are internal and external factors. Inflammation associated with bronchospasm involves damage to the smooth muscle of the bronchi resulting in shortness of breath accompanied by wheezing breath sounds. Narrowing of the airways causes shortness of breath and can have adverse effects on the sufferer. One of the non-pharmacological procedures that is easy to carry out and does not require costs, as well as side effects, is PLB and semi-Fowler position aimed at reducing shortness of breath in patients with bronchial asthma. This action is carried out 5-8 times for 15 minutes. This type of research uses descriptive case study research, the number of samples in the study is 1 patient. The results of the case study indicate that after performing purse lip breathing and semi-Fowler position for 15 minutes each day, within 3 days, as evidenced by a respiratory rate (RR) 22 x/minute and SpO₂: 99%.